Scrapbook Sebagai Media Edukasi Terhadap Pengetahuan Meal Plan dan Tingkat Konsumsi Ibu Hamil Dengan Anemia - Hidayat, Taufik; Kurniawan, Ahmad Rizqie; Saputra, Adisurya (Jurnal Keperawatan Florence Nightingale, 2024)
One of the efforts to prevent anemia in pregnant women is by increasing knowledge about healthy meal plans and consumption of iron and folic acid. Creative educational media, such as scrapbooks, can be an interactive and effective tool to convey important information about nutritious diets for pregnant women. This study aims to measure the effectiveness of using scrapbooks as an educational media in improving meal plan knowledge and food consumption levels in pregnant women with anemia. The research method used Pre Experiment with One Group Pre test-Post test. Sampling using purposive sampling consisted of 24 respondents (pregnant women with anemia). Data collection using questionnaires and food recall interviews for 3 non-consecutive days. Data analysis was carried out with the Wilcoxon test and the results showed that there was an effect of scrapbooks as an educational medium on Meal Plan knowledge of pregnant women with anemia with p value = 0.000 (p <0.05). While for consumption level variables there is no influence with anemia (energy p value = 0.133), (protein p value = 0.259), (fat p value = 0.116) and (carbohydrate p value = 0.61). The suggestions and implications of this study indicate that scrapbooks are not only effective in improving the knowledge and behavior of pregnant women related to meal plans, but also have a broad impact in public health practice, policy, and education. Implementation of the results of this study is expected to contribute.